Creative arts PhD : future-proofing the creative arts in higher education : scoping for quality in creative arts doctoral programs : project final report. - Baker, Su; Buckley, Brad; Kett, Giselle (Australian Learning and Teaching Council, 2009)
The Future-Proofing the Creative Arts in Higher Education Scoping Study was established to provide evidence-based understanding of doctoral studies in the creative arts in Australian universities upon which future developments in research training would be based, thus advancing strategic leadership in the sector. This study examined the research training conditions primarily in the Australian context and with some selected international examples. The project: provided an evidence-based understanding of PhD and the professional doctorate programs in the creative arts, and more specifically the visual arts in Australia; investigated corresponding programs in a sample of overseas universities; gained a national and international understanding of quality research training methods; identified models of thesis submission for the PhD and the professional doctorate; provided information to enable the establishment of benchmark standards of high quality creative arts doctoral supervision, research training, examination and outcomes; provided recommendations for ongoing cross-institutional and cross-sector collaboration in the design and development of creative arts doctoral studies; and disseminated the project findings through a project web site, liaison with peak bodies and key stakeholders. [Executive summary]